THE POTENTIAL OF A SOOTHING GEL OF YELLOW WATERMELON (Citrullus lanatus (Thunb.) AND CUCUMBER (Cucumis sativus L.) EXTRACT COMBINATION AS SUNSCREEN - Syarifah, Anisa Lailatusy; Yunita; Marisa, Ressa; Intansari, Chintya Ferda (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
People, particularly women with dry skin issues, want to apply sunscreen and skincare products to moisturize their skin. As a matter of fact, a formulation, that functions to moisturize is a soothing gel. A soothing gel formulation requires an active substance with a high water content, which can be obtained from fruits such as cucumbers and yellow watermelons. This study aimed to explore the potential of a soothing gel containing yellow watermelon and cucumber extract as a sunscreen, based on its Sun Protection Factor (SPF) value. Moreover, in this study, the yellow watermelon and cucumber extracts were processed using a juicer. Subsequently, a flavonoid test was conducted on the extract combination. The combination of yellow watermelon and cucumber extracts was formulated into a soothing gel at concentrations of 70%, 80%, and 90%. Furthermore, the SPF value of the soothing gel was determined in vitro using the UV-Vis spectrophotometry method. The results of this study showed that yellow watermelon and cucumber extracts, as well as their combination, contained flavonoid compounds. The highest SPF value, namely that of the soothing gel formula, was 80%. The SPF value of soothing gel formula 70%, 80%, and 90% respectively, was 3.5118±0.1969; 4.3771±0.4184; and 3.2274±0.2397. Hence, it can be concluded that, based on the SPF value, the combination of yellow watermelon and cucumber extracts in the soothing gel has potential as a sunscreen with medium protection. Keywords: Citrullus lanatus Thunb., Cucumis sativus L., yellow watermelon, soothing gel, sun protection factor